Curare e prendersi cura degli adolescenti ammalati di tumore: evoluzione di un modello di assistenza centrato sul paziente (Altre Modernità, 2020)
Adolescents with cancer are a particular group of patients with special needs. The paper describes the psychological impact of cancer on adolescent patients and introduces the “Youth Project” of the Pediatric Oncology Unit IRCCS Fondazione Istituto Nazionale Tumori in Milan, dedicated to young patients with solid tumors. This project represents a possible new assistance model to address the unique needs of patients in this age group.
Keywords: adolescent and young adults; cancer; pediatric oncology, psychological impact; model of care